Successful tocilizumab treatment in a patient with human herpesvirus 8‐positive and human immunodeficiency virus‐negative multicentric Castleman's disease of plasma cell type nonresponsive to rituximab‐CVP therapy. Issue 7 (20th November 2012) - Műzes, Györgyi; Sipos, Ferenc; Csomor, Judit; Sréter, Lídia
<x xml:space="preserve">Abstract</x> We present and discuss the case of a HIV‐negative female finally diagnosed upon histopathologic and molecular biologic evaluations with human herpesvirus 8 (HHV8)‐positive multicentric Castleman's disease (MCD) of plasma cell type, but with no detectable HHV8‐DNA in peripheral blood. She failed to respond to combination immunosuppressive therapeutic trials of corticosteroids and azathioprine, and neither an immunochemotherapy of rituximab‐CVP (R‐CVP) induced disease resolution. However, monoclonal anti‐IL‐6R antibody (tocilizumab) immunotherapy resulted in beneficial disease stabilization. A control lymph node biopsy indicated mild polyclonal plasmacytosis, and a negative HHV8 determination. The patient is still receiving tocilizumab. This case emphasizes the individual nature of MCD requiering more personalized disease management.